Validity and reliability of a self-administered foot evaluation questionnaire (SAFE-Q) - Niki, Hisateru (Springer Japan, 2013)
BACKGROUND: The Japanese Society for Surgery of the Foot (JSSF) is developing a QOL questionnaire instrument for use in pathological conditions related to the foot and ankle. The main body of the outcome instrument (the Self-Administered Foot Evaluation Questionnaire, SAFE-Q version 2) consists of 34 questionnaire items, which provide five subscale scores (1: Pain and Pain-Related; 2: Physical Functioning and Daily Living; 3: Social Functioning; 4: Shoe-Related; and 5: General Health and Well-Being). In addition, the instrument has nine optional questionnaire items that provide a Sports Activity subscale score. The purpose of this study was to evaluate the test-retest reliability of the SAFE-Q. PATIENTS AND METHODS: Version 2 of the SAFE-Q was administered to 876 patients and 491 non-patients, and the test-retest reliability was evaluated for 131 patients. In addition, the SF-36 questionnaire and the JSSF Scale scoring form were administered to all of the participants. Subscale scores were scaled such that the final sum of scores ranged between zero (least healthy) to 100 (healthiest). RESULTS: The intraclass correlation coefficients were larger than 0.7 for all of the scores. The means of the five subscale scores were between 60 and 75. The five subscales easily separated patients from non-patients. The coefficients for the correlations of the subscale scores with the scores on the JSSF Scale and the SF-36 subscales were all highly statistically significantly greater than zero (p < 0.001). The means for the five JSSF Scale classification groups fell within a relatively narrow range, indicating that the SAFE-Q labels are sufficiently similar to permit their use for all of the JSSF Scale classifications. CONCLUSION: The present study revealed that the test-retest reliability is high for each subscale. Consequently, the SAFE-Q is valid and reliable. In the future, it will be beneficial to test the responsiveness of the SAFE-Q.